2022
DOI: 10.1007/s10237-021-01534-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrated fluid–structure interaction and thrombosis model for type B aortic dissection

Abstract: False lumen thrombosis (FLT) in type B aortic dissection has been associated with the progression of dissection and treatment outcome. Existing computational models mostly assume rigid wall behavior which ignores the effect of flap motion on flow and thrombus formation within the FL. In this study, we have combined a fully coupled fluid–structure interaction (FSI) approach with a shear-driven thrombosis model described by a series of convection–diffusion reaction equations. The integrated FSI-thrombosis model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Furthermore, our simulation assumed a rigid wall. In a study using an idealised geometry, Chong et al (2022) demonstrated that accounting for wall compliance and flap motion can results in a 25% increase in the volume of thrombus formed. Flap stiffness varies from patient to patient, and tends to increase with the age of dissection ( Peterss et al, 2016 ), thus the flap may have been less mobile in this post-TEVAR case making the rigid wall assumption less impactful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our simulation assumed a rigid wall. In a study using an idealised geometry, Chong et al (2022) demonstrated that accounting for wall compliance and flap motion can results in a 25% increase in the volume of thrombus formed. Flap stiffness varies from patient to patient, and tends to increase with the age of dissection ( Peterss et al, 2016 ), thus the flap may have been less mobile in this post-TEVAR case making the rigid wall assumption less impactful.…”
Section: Discussionmentioning
confidence: 99%
“… Menichini and Xu’s 2016 model requires five partial differential equations to be solved alongside the Navier-stokes equations, meaning simulations take on the order of 1–2 weeks to complete depending on patient-specific details such as cardiac cycle length. The computational cost increases even more when considering structural wall mechanics by performing fluid-structure-interaction (FSI) simulations - Chong et al (2022) performed an integrated FSI-thrombus study in an idealised geometry with Menichini and Xu’s 2016 model, with simulations taking 2–3 months to complete.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombosis involves complex interlinked interactions between platelets, coagulation cascades, and the vascular wall (30). In this study, traditional hemodynamics parameters including WSS, OSI, and RRT did not precisely identified regions of thrombus formation, probably due to the lack of reflection of this complex reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we ignored the arterial deformation in the 3D calculation. Future studies may combine fluid-structure interaction (FSI) models with mass transport models of thrombus to more realistically predict thrombus formation in deformed vessels (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…To date, minor branches have virtually always been neglected in simulations of the aorta due to limitations in medical image resolution, computational power, and a lack of available research on appropriate boundary conditions. Segmental arteries have been included as structural supports in aortic Fluid-Structure Interaction (FSI) studies 11,16 , but without haemodynamic assessment. The Inferior Mesenteric Artery (IMA) and a selection of FLbranching intercostal arteries were recently included in a TBAD simulation 3 .…”
Section: Introductionmentioning
confidence: 99%